(3geY GdghGeYs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s
(3ChdgG (B:s
(3SHMGfc dG GMUi KfGA Ydjc CfJ ceG CKfjJ Ydi faSc hHYO aEf dfG JCdjakG ai GdYQHjI eSeGI HgeY GdghGeY ai TQM LeY GdLhGeY s
(3BNQgG (B:s
(3hefge ef jcJH JMJ GdMQa Gdeged MQakG UZjQkG eKdg Ch geRI Ch ahbg YdGeI Ch fHPI GUWdGMGJ dGgd GdMOjK hgPG BNQ eG JVefg LeY GdLhGeY s
(3GdfSNI HgG MhGTs
(3HChdg JedcGJs
(3efbhdI Yf fSNI HNW GdeUfa s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs